Gold content of ectomycorrhizal and saprobic macrofungi from non-auriferous and unpolluted areas - Borovicka, Jan; Randa, Zdenĕk; Jelínek, Emil (Mycological research, 2005)
Ectomycorrhizal and saprobic macrofungi growing in the wild were collected from non-auriferous and unpolluted areas and analyzed for gold. Gold was determined using long-term instrumental neutron activation analysis (INAA). In total, 154 samples, including 67 species of ectomycorrhizal fungi and 22 species of terrestrial saprobes, were examined. Gold contents of the both groups were mostly less than 20 ng g(-1) of D.W. The highest concentrations (expressed in D.W.) were found in the ectomycorrhizal species Amanita strobiliformis (136 ng g(-1)), Russula claroflava (148 ng g(-1)), Cantharellus lutescens (156 and 210 ng g(-1)), and Boletus edulis (235 ng g(-1)). Among the saprobic fungi, the highest values were found in Langermannia gigantea (160 ng g(-1)) and Morchella esculenta (189 ng g(-1)). Species of Agaricus commonly had relatively high gold values, 10s of ng g(-1). The gold content of macrofungal fruit bodies was considerably higher than that of vascular plants, and parallels concentrations found in plants growing in auriferous areas.
Keywords: těžké kovy; mykorhiza; zlato; Gold; Metals, Heavy; látky znečišťující půdu; Environmental Monitoring; Fungi; Mycorrhizae; Soil Pollutants; houby; monitorování životního prostředí